Effect of multipulses exposure on excimer laser annealed polycrystalline silicon thin films - Bidin, Noriah (Institute of Electrical and Electronics Engineers, 2011)
Silicon thin film (STF) is widely used as a transistor. It performance depends on its crystal structure. The larger the crystallization of STF the better the current flow. The goal of this work is to anneal the STF using laser ablation technique. In this attempt, an amorphous silicon thin film was prepared by low pressure physical vapour deposition (PVD) and dopant by cooper. Initially the silicon film was heat treatment by a conventional method for four hours under temperature of 350°?C. The treated silicon film was then annealed by using ultraviolet light of argon fluoride (ArF) excimer laser, at variable energy density. The structure of thin film was observed using metallurgical technique via Atomic Force Microscope (AFM). The results obtained indicated that, the grain size of the a-Si film is increased via laser fluence or so-called energy density. The optimum grain size obtained is 143 nm corresponding to laser fluence of 345?mJcm-2.345?mJcm-2. Further exposure to higher fluence cause reduction in crystallization due to penetration into substrate.